Umowy celne i handlowe podpisane przez Unię Europejską z krajami trzecimi - konsekwencje dla Polski - Adamczyk, Marzena (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The accession to the European Union had a great influence on the Polish economy and substantially changed Polish authorities competence. In joint trade policy area all competence has been moved from country level to European Union level. One of the aspects of joint trade policy was taking over of all EU international customs and trade agreements and common customs tariffs. As a consequence the liberalization of the Polish economy became more intense and the economy itself became more open for international competition. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1147, s. 19-29